Prognostic assessment of gastric cancer: retrospective analysis of two decades - Mita, Maria Teresa; Marchesi, Federico; Cecchini, Stefano; Tartamella, Francesco; Ricco', Matteo; Abongwa, Hariscine Keng; Roncoroni, Luigi (Acta Biomedica Atenei Parmensis, 2016)
Background: Gastric cancer mortality rates have remained relatively unchanged over the past decades, in spite of progressive decrease in incidence. Nodal status represents a key factor for prognostic assessment, allowing a tailored-made adjuvant therapy for the patients. The aim of this study is to evaluate the prognostic influence of different nodal involvement indicators on the overall survival in a large series of patients submitted to gastrectomy at our Institution. Methods: we retrospectively collected data from 634 newly diagnosed patients with gastric cancer who underwent curative gastrectomy, with D1/D2 lymphadenectomy during the last 20 years. Prognostic values of age, histologic type, pN, nodal ratio (LNR) and log odds of positive lymph nodes (LODDS) of were analyzed. Results: The median overall survival was 40.2 +/-31 months. Multivariate analysis identified age at diagnosis, diffuse-type tumor, pN and LODDS as independent predictors of worse prognosis. Scatter plots of relationships between LODDS and LNR showed that LODDS seems to better assesses prognosis for patients at LNR stage 0 or 1. Conclusions: Nodal involvement confirmed to be a strong indicator of prognosis. LODDS demonstrated a theoretical advantage over pN and LNR system allowing more accurate patients stratification, but our results have to be confirmed by further trials.